ICU nurse preceptors' perceptions of benefits, rewards, supports and commitment to the preceptor role: A mixed-methods study. (February 2021) - Macey, Andy; Green, Cameron; Jarden, Rebecca J.
Abstract: This paper explores Intensive Care nurses' perceptions of benefits, rewards, supports and their commitment to the role of preceptor. A questionnaire, consisting of Likert-scales and open-ended questions was used to collect data during October 2018. Preceptors were committed to their role. Correlations were found between preceptors' perceptions of benefits or rewards and commitment to the role ( p = 0.003, r 2 = 0.39) and perceptions of support and commitment to the role ( p = . 001, r 2 = 0.46). Altruistic benefits were perceived to be of the greatest importance. Participants who recognised the importance of preceptorship for the organisation were more likely to be committed to the role. Eighty-three percent of respondents reported a lack of consistency in allocation to work with their preceptee. Qualitative results elucidated themes of helping, personal professional development, the opportunity to teach, and organisational improvement. Supports as barriers and enablers to successful preceptorship were discussed in terms of peer and leadership support, role preparation, the logistics of the environment, role conflict, and consistency of allocation to work in a preceptorship dyad. Commitment to the preceptor role may be increased by highlighting organisational benefits of preceptorship, increasing consistency of contact between preceptorship dyads, and increasing access to supports and preparation. Highlights: ICU nurse preceptors value the altruistic benefits of preceptorship . Commitment is increased when organisational benefits are recognised. ICU preceptors report a lack of consistency and support in their role.